Razvoj vsakodnevnih aktivnosti pri otroku s prirojeno obojestransko pomanjkljivostjo zgornjih udov - Brezovar, Darinka (Rehabilitacija (Ljubljana), 2019)
Rehabilitation of a child with complete absence of the upper limb requires a comprehensive team approach. The plan of rehabilitation is prepared and adjusted based on initial and follow-up assessments of functional abilities. It comprises the neurodevelopmental program with a biomechanical approach and later on, development and searching for alternative strategies for activities of daily life. The long-term goal is the independence of the child in all areas of life. In the article, we present a case of a child with bilateral congenital upper limbs dysmelia. He was fitted with body-powered prosthesis for disarticulation in right shoulder. The function of two long fingers, growing out of left shoulder, improved over time. The analysis of his development of daily life activities showed significant delay from six months up to two years in comparison to the normal development. Based on results of evaluation with the Paediatric Evaluation of Disability Inventory (PEDI), he was significantly delayed in the self-care domain (results between 10th to 19th percentile). By the age of 12 years, he was still not able to be independent in some activities of daily life.
Keywords: bilateral dysmelia; Child; daily life activities; dnevne aktivnosti; habilitacija; habilitation; obojestranska dismelija; Ocupational Therapy; otrok; rehabilitation; Upper Extremity Deformities, Congenital; upper limb; zgornji ud